FACEBOOK Pertemanan Global Hingga Ikatan Personal - A. Dian Fitriana; Mifda Hilmiyah (KOMUNIDA : Media Komunikasi dan Dakwah, 2020)
Various supporting features of interpersonal communication and interaction such as chatrooms, walls, messanger, etc. make Facebook as one of the models of interpersonal mediated communication (interpersonal mediated communication). The purpose of this study is to describe the use of Facebook as a facility that facilitates friendship and personal relationships. The subject of this research is Facebook active users who utilize various Facebook features to meet new people. This study uses a qualitative method with a phenomenological approach. The results showed that various Facebook features were able to facilitate its users in communicating both socially just friends to personal communication that led to institutional (marriage). Keywords: Facebook; Global Friendship; Personal Bond